2017
DOI: 10.1590/1519-6984.11615
|View full text |Cite
|
Sign up to set email alerts
|

First record of Craspedacusta sowerbii Lankester, 1880 (Hydrozoa, Limnomedusae) in a natural freshwater lagoon of Uruguay, with notes on polyp stage in captivity

Abstract: The freshwater cnidarian Craspedacusta sowerbii Lankester 1880, has invaded lakes and ponds as well as artificial water bodies throughout the world. The first record in Uruguay corresponding to the jellyfish was made in 1961 in two artificial fountains, with no mention of the polyp form. Although local reports of other related polyp species have been made, information on the benthic form of C. sowerbii is lacking. Here we report the finding of live frustules, solitary individuals, medusae and colonies from a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Polyps of C. sowerbii were recorded in the lake on the zebra mussels D. polymorpha in shallow water and on the undersides of artificial substrates. The polyp and medusa stages are only rarely reported together in the same aquatic ecosystem (Failla Siquier et al, 2017). Considering the commensalism between polyps of C. sowerbii and D. polymorpha described by Stanković and Ternjej (2010), the analyses of zebra mussels could be a simple method to check for the presence of C. sowerbii in various aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyps of C. sowerbii were recorded in the lake on the zebra mussels D. polymorpha in shallow water and on the undersides of artificial substrates. The polyp and medusa stages are only rarely reported together in the same aquatic ecosystem (Failla Siquier et al, 2017). Considering the commensalism between polyps of C. sowerbii and D. polymorpha described by Stanković and Ternjej (2010), the analyses of zebra mussels could be a simple method to check for the presence of C. sowerbii in various aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…It is a cosmopolitan invasive taxon, occuring in all continents except Antarctica (Dumont, 1994;Jankowski, 2001;Jankowski et al, 2008). After its discovery in England, the taxon was recorded in numerous other European countries (Arbačiauskas and Lesutienė, 2005;Lundberg et al, 2005;Fritz et al, 2007;Karaouzas et al, 2015;Minchin et al, 2016;Ciutti et al, 2017;Medina-Gavilán and González-Duarte, 2018), in North America (Acker and Muscat, 1976;DeVries, 1992), in Central America (Moreno-Leon and Ortega-Rubio, 2009), in South America (Failla Siquier et al, 2017;Caputo et al, 2018), in Asia (Bekleyen et al, 2011;Gasith et al, 2011;Lewis et al, 2012); in Africa (Rayner, 1988;Oualid et al, 2019), in Australia (Thomas, 1950) and in New Zealand (Boothroyd et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with Oualid et al (2019), 16S and ITS analyses showed at least 4 main Craspedacusta lineages. According to the identification provided by the different authors to the sequences used (Zhang et al 2009, Zou et al 2012), these species are C. sinensis (for the moment only reported from China), C. ziguiensis (only from China), and 2 separate widespread lineages mainly attributed to C. sowerbii (Collins et al 2008, Fritz et al 2009, Zhang et al 2009, Stefani et al 2010, Zou et al 2012, Karaouzas et al 2015, Failla Siquier et al 2017, Riyas & Kumar 2017, Fuentes et al 2019, Oualid et al 2019. The divergent Cox1 sequence MF000493 from Switzerland could be incorrect -perhaps a nuclear pseudogene, as the 16S sequence places it within one of the 2 main C. sowerbii clades (P. Schuchert pers.…”
Section: Morphological and Phylogenetic Remarks On Bc's Craspedacustamentioning
confidence: 99%
“…These diapausing stages thus facilitate human-mediated dispersal with fish stocking, relocation of aquatic plants and invertebrates, or passive dispersal through waterfowl, mammals and other animals (Incagnone et al 2015;Failla Siquier 2017). While the polyp form dominates its lifehistory, the three other stages (medusa, frustule, resting body) occur in response to specific environmental conditions (Acker and Muscat 1976).…”
Section: Introductionmentioning
confidence: 99%